Modelo de gestão para institutos de pesquisa, desenvolvimento e inovação - Garlet, Taís Bisognin (2017)
The fulfillment of research, development and innovation projects has been encouraged in the last few years aiming to stimulate the generation and application of knowledge focused on new products, processes and technologies. These projects are considered solutions for creating high level technological content, besides providing economical growth through adding barriers against competing organizations. Purposing to promote scientific, technological and innovation developing, governmental organizations have encouraged cooperation between companies and institutes that hold research, development and innovation projects to foster technologies and knowledge exchange. The connection between institutes and industrial companies needs to happen intending to fill the gaps in the business sector, attending demands in innovation projects, and to plan the projects, perform and control resources usage. So, it is vital that institutes present an effective and efficient management model. Thus, this dissertation project aims to propose a management model based on performance evaluation systems for institutes that carry out research, development and innovation activities. In order to reach the objective, this qualitative research was based on a bibliographical and documentary review about this sector features, performance evaluation systems and elements that originated a management model composed of eight phases, which was tested at the Institute of Smart Grids (INRI). Based on the results analysis, it is possible to state that the proposed organizational management model presents potential for better planning and control of the projects, resources usage optimization, risks reduction and agility on failures identification.